2014
DOI: 10.1155/2014/615840
|View full text |Cite
|
Sign up to set email alerts
|

Solving a Class of Singularly Perturbed Partial Differential Equation by Using the Perturbation Method and Reproducing Kernel Method

Abstract: We give the analytical solution and the series expansion solution of a class of singularly perturbed partial differential equation (SPPDE) by combining traditional perturbation method (PM) and reproducing kernel method (RKM). The numerical example is studied to demonstrate the accuracy of the present method. Results obtained by the method indicate the method is simple and effective.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(5 citation statements)
references
References 24 publications
0
5
0
Order By: Relevance
“…2 The superiority of the proposed methods could be established in the table above. From the table above, it could also be From table 6 above, it could also be observed that the Method shows some superiority in-terms of accuracy when compared with the method of Wang et al [11] and also compares favourably 3 (x, t) is the coordinate of x and t, u(x, t) is the exact solution, UM is the Upwind method, LM is the Lax method, Method represents the solution using the Method and Relative error=| u(x, t) -Method |/u(x, t). Percentage error = Relative error × 100%.…”
Section: Tables Of Results and Comparisonmentioning
confidence: 78%
See 3 more Smart Citations
“…2 The superiority of the proposed methods could be established in the table above. From the table above, it could also be From table 6 above, it could also be observed that the Method shows some superiority in-terms of accuracy when compared with the method of Wang et al [11] and also compares favourably 3 (x, t) is the coordinate of x and t, u(x, t) is the exact solution, UM is the Upwind method, LM is the Lax method, Method represents the solution using the Method and Relative error=| u(x, t) -Method |/u(x, t). Percentage error = Relative error × 100%.…”
Section: Tables Of Results and Comparisonmentioning
confidence: 78%
“…In this section, the standards methods of Upwind, Lax method, the method of Wang et al [11] and the Method were employed successfully for solving the advection equations. The numerical results of the proposed method show some superiority over other methods in-terms of accuracy and reliability.…”
Section: Tables Of Results and Comparisonmentioning
confidence: 99%
See 2 more Smart Citations
“…e area of SP is a field of increasing interest to applied mathematicians and computer mathematics scientists. During the last decades, considerable contributions on the topic and its applications have been made by several researchers [1,[32][33][34][35][36][37][38][39][40][41]. Note that considerable research work in special topics of SP nonlinear differential equations has been recently presented [16][17][18][19][20][21].…”
Section: Sp Nonlinear Parabolic/elliptic Differential Equationsmentioning
confidence: 99%